Femininity, science, and the denigration of the girly girl. Issue 8 (17th November 2017) - Francis, Becky; Archer, Louise; Moote, Julie; de Witt, Jen; Yeomans, Lucy
Abstract: Hyper-femininity and the construction of the 'girly girl' label have been documented widely, but there has been less attention to their content (or any distinctions between these constructs). Indeed, it can be argued that the content of femininity remains a controversial and somewhat under-researched topic in feminist scholarship. This is also the case in relation to science, which has been widely characterised as a masculine terrain, but there has been less attention to why femininity is excluded from/by science. This article attempts to unpick some of these issues, with a particular focus on the construct of the 'girly girl', in relation to access to science. Drawing on qualitative data from the Economic and Social Research Council-funded ASPIRES 2 project, we analyse the discourses used by young people and parents in discussion of 'girly girls' and physics. We show the misogynist and excluding discourses projected onto the 'girly girl', and indeed that are used to interpolate femininity more broadly. We found that in discussions of science and (hyper-)femininity, even potentially positive feminine attributes were denigrated. Hyper-femininity was produced as 'more than lack': vacuous, but also a risible presence. In reflecting on our findings we consider whether femininity may be more derided in some discursive contexts (e.g. science discourse) than others, and whether femininity can or should be conceived as more than lack.